Metal ceramic with double-layer surface structure and preparation method thereof

By designing a double-layer surface structure in a cermet tool, the nitrogen partial pressure and temperature gradient are controlled by the sintering process to form a structure with high solid solubility and high wear resistance, the metal cermet tool is solved to resist collapse under high temperature and high speed cutting conditions. The problem of poor performance extends the tool life and improves impact resistance.

CN118880145BActive Publication Date: 2025-01-03GANZHOU ACHTECK TOOL TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411382976.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Metal cermet tools have poor melting resistance under high temperature and high speed cutting conditions, and are prone to small melting holes that lead to large melting of the blade, affecting the tool life and the surface finish of the processed parts.

Method used

Metal cermet adopts a double-layer surface structure, including the first surface area, the second surface area and the homogeneous region from the outside and the inside, the first surface area has a relatively black-limited core and a core with an isometric crystalline morphology. The ring structure, the second surface area has relatively black grains and partly a core core structure, and the homogeneous area has a uniform distribution core ring structure. The nitrogen partial pressure and temperature gradient are controlled through the sintering process to form high solid solubility and high wear resistance. Performance structure.

Benefits of technology

It reduces the chance of tiny collapse in the initial cutting stage, extends the cutting life of the tool, improves impact resistance and comprehensive performance, and maintains the hardness and collapse resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118880145B_ABST
    Figure CN118880145B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal ceramics, and specifically relates to a metal ceramic with a double-layer surface structure and a preparation method thereof, wherein the metal ceramic includes a first surface layer area, a second surface layer area, and a homogeneous layer area from the outside to the inside in sequence; the first surface layer area presents a core ring structure with a relatively poor black core and grains of equiaxed crystal morphology; the second surface layer area presents relatively rich black grains, and some of the grains are core-core structures; the homogeneous layer area presents a uniformly distributed core ring structure. The first surface layer area reduces the probability of micro-cracks when the tool contacts the workpiece in the initial cutting stage, and hinders the extension of the crack phase inside the material; during continuous and stable cutting, the second surface layer area can ensure a good cutting life of the tool; the homogeneous layer area presents a uniformly distributed core ring structure with both hardness and anti-crack damage, maintaining the good comprehensive performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal ceramics, and in particular relates to a metal ceramic with a double-layer surface structure and a preparation method thereof. Background Art

[0002] Ti(C,N)-based cermets are upgraded alternative materials for cemented carbide materials. With their higher wear resistance, lower friction coefficient between metals, better high temperature performance and oxidation resistance, cermet tools can be well adapted to high-speed, high-precision and continuous, dry cutting with larger feed volume, greatly improving cutting efficiency and service life. Ti(C,N)-based cermets are made by powder metallurgy using soft transition metals (Ni, Co) bonded with ceramic matrix phases such as TiC, TiN, Ti(C,N) and secondary carbides (such as Mo2C, WC, TaC, etc.). Compared with cemented carbide tools, they have better affinity for iron and high temperature strength. They are a composite material with high hardness and high wear resistance. They are widely used in the field of high-speed precision cutting to obtain good surface finish. However, with the current demand for increasing processing efficiency, the poor anti-breakage property of cermets under high-temperature and high-speed cutting conditions has been highlighted. It is easy to cause large breakage of the blade due to small breakage, which reduces the tool life and affects the surface finish of the workpiece. Therefore, the material properties of metal ceramic tools currently used to solve the problem of micro-breakage resistance in processing steel materials still need to be improved. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a metal ceramic with a double-layer surface structure and a preparation method thereof.

[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0005] A metal ceramic with a double-layer surface structure, the metal ceramic comprising a first surface layer region, a second surface layer region, and a homogeneous region from the outside to the inside;

[0006] The first surface region presents a core-ring structure with a relatively black core and grains of equiaxed crystal morphology;

[0007] The second surface area is relatively rich in black grains, and some of the grains are core-core structures;

[0008] The homogeneous area presents a uniformly distributed core ring structure.

[0009] As a preferred solution of the metal ceramic with a double-layer surface structure described in the present invention, the core ring structure of the homogeneous zone is a black core-gray ring structure or a white core-gray ring structure.

[0010] As a preferred embodiment of the metal ceramic with a double-layer surface structure described in the present invention, the thickness of the first surface layer is 2-10 μm, and the thickness of the second surface layer is 0.5-5.0 μm.

[0011] As a preferred embodiment of the metal ceramic with a double-layer surface structure described in the present invention, the equiaxed crystal morphology refers to a grain aspect ratio of 1.0 to 1.8, preferably 1.0 to 1.3.

[0012] As a preferred embodiment of the metal ceramic with a double-layer surface structure described in the present invention, the first surface region is further coated with at least one nano-alternating layer of AlCrXN and TiSiMN, or at least one nano-alternating layer of AlCrN and TiSiMN, or at least one nano-alternating layer of AlCrXN and TiSiN; X is at least one of C, O, B, Si, Ti, Zr, Hf, V, W, Y, and Ce; M is at least one of C, O, B, Al, Zr, Hf, V, W, Y, and Ce; the thickness of the nano-alternating layer is 20-50 nm, and the total thickness of the coated coating is 2-4 μm.

[0013] As a preferred embodiment of the metal ceramic with a double-layer surface structure described in the present invention, the average grain size of the first surface area of ​​the metal ceramic with a double-layer surface structure is 1~3μm; the grain size of the second surface area is 0.6~1.5μm; the hardness of the homogeneous area HRA is 90.8~91.6; the hardness of the first surface area HRA is 90.4~91.2; and the hardness of the second surface area HRA is 91.2~92.0.

[0014] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0015] A method for preparing a metal ceramic having a double-layer surface structure comprises the following steps:

[0016] S1, mixing the raw materials, solvent and forming agent, ball milling and spray granulation to obtain a mixed material;

[0017] S2, pressing the mixed material into a compact to obtain a green compact;

[0018] S3. Place the compact in a vacuum atmosphere, heat it to the forming agent removal temperature, remove the forming agent, then heat the compact from which the forming agent has been removed to temperature A in atmosphere A and sinter it, then adjust the temperature to temperature B in atmosphere B and sinter it, then cool it to room temperature in atmosphere C to obtain a metal ceramic with a double-layer surface structure.

[0019] As a preferred embodiment of the method for preparing a metal ceramic with a double-layer surface structure described in the present invention, it further includes step S4, coating at least one layer of a nano-alternating layer of AlCrXN and TiSiMN, or at least one layer of a nano-alternating layer of AlCrN and TiSiMN, or at least one layer of a nano-alternating layer of AlCrXN and TiSiN outside the first surface area; the X is at least one of C, O, B, Si, Ti, Zr, Hf, V, W, Y, and Ce; the M is at least one of C, O, B, Al, Zr, Hf, V, W, Y, and Ce; the thickness of the nano-alternating layer is 20-50 nm, and the total thickness of the coated coating is 2-4 μm.

[0020] As a preferred embodiment of the method for preparing a metal ceramic with a double-layer surface structure described in the present invention, in which: in the step S1, the raw material includes hard phase powder and binding phase powder, the mass of the hard phase powder accounts for 75~90wt% of the total mass of the raw material, and the mass of the binding phase powder accounts for 10~25wt% of the total mass of the raw material.

[0021] As a preferred embodiment of the method for preparing a metal ceramic with a double-layer surface structure described in the present invention, wherein: in the step S1, the hard phase powder is selected from at least one of carbide powder, nitride powder or carbonitride powder containing one or more of Ti, W, Ta, Nb, Cr, Mo, V, Mn, Hf and their solid solution powders; the binding phase powder is selected from at least one of cobalt, nickel and iron; the molding agent is selected from at least one of 48#-56# paraffin and PEG1000-PEG20000; and the solvent is anhydrous ethanol.

[0022] As a preferred embodiment of the method for preparing a metal ceramic with a double-layer surface structure described in the present invention, wherein: in the step S1, the particle size of the hard phase powder and the bonding phase powder is less than 1.8 μm.

[0023] As a preferred embodiment of the method for preparing a metal ceramic with a double-layer surface structure described in the present invention, in step S3, the forming agent removal temperature is 1200°C.

[0024] As a preferred embodiment of the method for preparing a metal ceramic with a double-layer surface structure described in the present invention, wherein: in the step S3, the A atmosphere is a nitrogen partial pressure gas of 10~100mbar; the heating rate is 5~7℃ / min, the A temperature is 1430~1550℃, and the A temperature sintering time is 30~120min.

[0025] As a preferred embodiment of the method for preparing a metal ceramic with a double-layer surface structure described in the present invention, in step S3, the B atmosphere is a nitrogen partial pressure gas of 2-50 mbar, the B temperature is 1350-1400°C, and the B temperature sintering time is 30-60 min.

[0026] As a preferred embodiment of the method for preparing a metal ceramic with a double-layer surface structure described in the present invention, in step S3, the C atmosphere is an argon atmosphere of 2-10 bar.

[0027] The beneficial effects of the present invention are as follows:

[0028] The present invention proposes a metal ceramic with a double-layer surface structure and a preparation method thereof. The metal ceramic includes a first surface layer zone, a second surface layer zone, and a homogeneous layer zone from the outside to the inside; the first surface layer zone presents a core-ring structure with a relatively black-poor core and grains with an equiaxed crystal morphology; the second surface layer zone presents relatively black-rich grains, and some of the grains are a core-core structure; and the homogeneous layer zone presents a uniformly distributed core-ring structure. The first surface zone has a relatively black-poor core and a core-ring structure with equiaxed crystal morphology, and the organizational composition has high solid solubility of elements such as W, Ti, Ta, Nb, and V. This structure has a high thermal vibration resistance gradient in the material, which reduces the probability of micro-chipping when the tool contacts the workpiece in the initial cutting stage, and hinders the extension of the crack phase inside the material; the second surface zone has relatively black-rich grains, and some grains are core-core structures. The carbide, nitride, and carbonitride phases of Ti make the material structure have a high wear resistance gradient. During continuous and stable cutting, the second surface zone can ensure a good cutting life of the tool; the homogeneous zone has a uniformly distributed core-ring structure that has both hardness and chipping resistance, maintaining the good comprehensive performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0030] Figure 1 This is a cross-sectional view of the metal ceramic of Example 1 of the present invention.

[0031] Figure 2 for Figure 1 Magnified image of .

[0032] In the figure, 1-first surface area, 2-second surface area, 3-homogeneous area.

[0033] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0034] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] According to one aspect of the present invention, the present invention provides the following technical solution:

[0036] A metal ceramic with a double-layer surface structure, the metal ceramic comprising a first surface layer region, a second surface layer region, and a homogeneous region from the outside to the inside;

[0037] The first surface region presents a core-ring structure with a relatively black core and grains of equiaxed crystal morphology;

[0038] The second surface area is relatively rich in black grains, and some of the grains are core-core structures;

[0039] The homogeneous area presents a uniformly distributed core ring structure.

[0040] The present invention is based on the strong coupling effect of Ti-N. During the sintering process, the nitrogen in the nitride and carbonitride of Ti in the organization is continuously decomposed. Under a larger nitrogen partial pressure in the furnace, when the nitrogen concentration on the surface of the material is balanced with the nitrogen pressure in the furnace, the nitrogen concentration on the surface is higher than the nitrogen concentration inside the material, and Ti migrates to the surface first. The high nitrogen concentration makes the alloy elements "dissolve-precipitate" in the core of the hard phase of the Ti (C, N)-based cermet insufficient, inhibiting the formation of annular phases with high W and Mo contents, causing the thickness of the annular phases to become thinner, making more The alloy elements are dissolved in the bonding phase to form relatively black-rich grains or / and a structural area with a core-core structure; then the nitrogen partial pressure is reduced and the sintering time is controlled during the sintering process to reduce the saturated vapor pressure on the surface of the green body, and the N in the Ti-rich nitrides and carbonitrides previously formed in the surface layer is decomposed from the surface to the inside, Ti migrates to the inside again, and the annular phase is "precipitated" again, and the first surface area gradually forms a structure with a relatively poor black core, and the second surface area presents relatively black-rich grains, and some of the grains have a core-core structure.

[0041] Preferably, the core ring structure of the homogeneous zone is a black core-gray ring structure or a white core-gray ring structure.

[0042] Preferably, the thickness of the first surface layer is 2-10 μm, and the thickness of the second surface layer is 0.5-5.0 μm.

[0043] Preferably, the equiaxed crystal morphology refers to a grain aspect ratio of 1.0 to 1.8, preferably 1.0 to 1.3.

[0044] Preferably, at least one layer of nano-alternating layer of AlCrXN and TiSiMN, or at least one layer of nano-alternating layer of AlCrN and TiSiMN, or at least one layer of nano-alternating layer of AlCrXN and TiSiN is coated outside the first surface region; X is at least one of C, O, B, Si, Ti, Zr, Hf, V, W, Y, and Ce; M is at least one of C, O, B, Al, Zr, Hf, V, W, Y, and Ce; the thickness of the nano-alternating layer is 20-50 nm, and the total thickness of the coated coating is 2-4 μm.

[0045] Preferably, the average grain size of the first surface area of ​​the metal ceramic with a double-layer surface structure is 1~3μm; the grain size of the second surface area is 0.6~1.5μm; the hardness of the homogeneous area HRA is 90.8~91.6; the hardness of the first surface area HRA is 90.4~91.2; and the hardness of the second surface area HRA is 91.2~92.0.

[0046] According to another aspect of the present invention, the present invention provides the following technical solution:

[0047] A method for preparing a metal ceramic having a double-layer surface structure comprises the following steps:

[0048] S1, mixing the raw materials, solvent and forming agent, ball milling and spray granulation to obtain a mixed material;

[0049] S2, pressing the mixed material into a compact to obtain a green compact;

[0050] S3. Place the compact in a vacuum atmosphere, heat it to the forming agent removal temperature, remove the forming agent, then heat the compact from which the forming agent has been removed to temperature A in atmosphere A and sinter it, then adjust the temperature to temperature B in atmosphere B and sinter it, then cool it to room temperature in atmosphere C to obtain a metal ceramic with a double-layer surface structure.

[0051] Preferably, the method further comprises step S4, coating at least one layer of nano-alternating layer of AlCrXN and TiSiMN, or at least one layer of nano-alternating layer of AlCrN and TiSiMN, or at least one layer of nano-alternating layer of AlCrXN and TiSiN outside the first surface layer area; X is at least one of C, O, B, Si, Ti, Zr, Hf, V, W, Y, and Ce; M is at least one of C, O, B, Al, Zr, Hf, V, W, Y, and Ce; the thickness of the nano-alternating layer is 20-50 nm, and the total thickness of the coated coating is 2-4 μm.

[0052] Preferably, in step S1, the raw material includes hard phase powder and binder phase powder, the mass of the hard phase powder accounts for 75-90wt% of the total mass of the raw material, and the mass of the binder phase powder accounts for 10-25wt% of the total mass of the raw material.

[0053] Preferably, in step S1, the hard phase powder is selected from at least one of carbide powder, nitride powder or carbonitride powder containing more than one of Ti, W, Ta, Nb, Cr, Mo, V, Mn, Hf and their solid solution powders; the binder phase powder is selected from at least one of cobalt, nickel and iron; the molding agent is selected from at least one of 48#-56# paraffin and PEG1000-PEG20000; and the solvent is anhydrous ethanol.

[0054] Preferably, in step S1, the particle size of the hard phase powder and the binder phase powder is less than 1.8 μm.

[0055] Preferably, in step S3, the forming agent removal temperature is 1200°C.

[0056] Preferably, in step S3, atmosphere A is a nitrogen partial pressure gas of 10-100 mbar; the heating rate is 5-7°C / min, temperature A is 1430-1550°C, and sintering time at temperature A is 30-120 min.

[0057] Preferably, in step S3, the B atmosphere is a nitrogen partial pressure gas of 2-50 mbar, the B temperature is 1350-1400° C., and the B temperature sintering time is 30-60 min.

[0058] Preferably, in step S3, the C atmosphere is an argon atmosphere at 2-10 bar.

[0059] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0060] Example 1

[0061] A method for preparing a metal ceramic having a double-layer surface structure comprises the following steps:

[0062] S1. The raw materials include cobalt powder and nickel powder as binder phase powder, titanium-containing cubic carbonitride powder and carbide powders of tungsten, tantalum, niobium, molybdenum and vanadium as hard phase powders. The mass percentage of each raw material is as follows: binder phase powder (the mass ratio of cobalt powder and nickel powder is 1:1) 15wt%, tantalum and niobium carbide powders (the mass ratio of tantalum carbide and niobium carbide is 4:1) 15wt%, molybdenum carbide powder 5wt%, vanadium carbide powder 2wt%, titanium-containing cubic carbonitride 55wt%, and the remainder is tungsten carbide powder. The particle size of each powder is <1.8 μm. The above raw materials, solvent (using anhydrous ethanol as solvent) and molding agent (using paraffin as molding agent, the addition amount is 2wt% of the total mass of the raw materials) are mixed and ball-milled, and spray granulated to obtain a mixture.

[0063] S2, pressing the mixed material into a compact to obtain a green compact;

[0064] S3. The compact is placed in a vacuum atmosphere, heated to 1200°C, introduced with a nitrogen partial pressure of 40 mbar, and then sintered to 1470°C at a heating rate of 6°C / min in a nitrogen atmosphere, and kept warm for 90 minutes. Thereafter, the nitrogen partial pressure is adjusted to 20 mbar, the temperature is adjusted to 1400°C and sintered for 10 minutes. Thereafter, a 5 bar argon atmosphere is filled and cooled to room temperature to obtain a metal ceramic with a double-layer surface structure.

[0065] The metal ceramic with a double-layer surface structure obtained in this embodiment (its cross section is as follows Figure 1-2 As shown in the figure, 1 is the first surface area, 2 is the second surface area, and 3 is the homogeneous area) is cut and formed to form a rough tool blank, and the cutting edge of the tool is rounded using a nylon brush containing SiC, and then an AlCrN+TiSiN nano-alternating coating (nanolayer thickness is 30nm, coating thickness is 3μm) is deposited on the surface of the substrate to obtain tool A1.

[0066] Example 2

[0067] A method for preparing a metal ceramic having a double-layer surface structure comprises the following steps:

[0068] S1. The raw materials include cobalt powder and nickel powder as binder phase powder, titanium-containing cubic carbonitride powder and carbide powders of tungsten, tantalum, niobium, molybdenum and vanadium as hard phase powders. The mass percentage of each raw material is as follows: binder phase powder (the mass ratio of cobalt powder and nickel powder is 2:1) 19wt%, tantalum and niobium carbide powders (the mass ratio of tantalum carbide and niobium carbide is 4:1) 15wt%, molybdenum carbide powder 5wt%, vanadium carbide powder 2wt%, titanium-containing cubic carbonitride 51wt%, and the remainder is tungsten carbide powder. The particle size of each powder is <1.8 μm. The above raw materials, solvent (using anhydrous ethanol as solvent) and molding agent (using paraffin as molding agent, the addition amount is 2wt% of the total mass of the raw materials) are mixed and ball-milled, and spray granulated to obtain a mixture.

[0069] S2, pressing the mixed material into a compact to obtain a green compact;

[0070] S3. Place the compact in a vacuum atmosphere, heat it to 1200°C, introduce 40 mbar nitrogen partial pressure, then heat it to 1500°C at a heating rate of 6°C / min in a nitrogen atmosphere and sinter it for 90 minutes. Then adjust the nitrogen partial pressure to 20 mbar, adjust the temperature to 1400°C and sinter it for 10 minutes. Then fill it with 5 bar argon atmosphere and cool it to room temperature to obtain a metal ceramic with a double-layer surface structure.

[0071] The metal ceramic with a double-layer surface structure obtained in this embodiment is cut and formed to form a rough tool blank, and the cutting edge of the tool is rounded using a nylon brush containing SiC. Thereafter, an AlCrN+TiSiN nano-alternating coating (nanolayer thickness is 20 nm, coating thickness is 2 μm) is deposited on the surface of the substrate to obtain tool A2.

[0072] Example 3

[0073] A method for preparing a metal ceramic having a double-layer surface structure comprises the following steps:

[0074] S1. The raw materials include cobalt powder and nickel powder as binder phase powder, titanium-containing cubic carbonitride powder and carbide powders of tungsten, tantalum, niobium, molybdenum and vanadium as hard phase powders. The mass percentage of each raw material is as follows: binder phase powder (the mass ratio of cobalt powder and nickel powder is 2:1) 19wt%, tantalum and niobium carbide powders (the mass ratio of tantalum carbide and niobium carbide is 3:1) 13wt%, molybdenum carbide powder 5wt%, vanadium carbide powder 2wt%, titanium-containing cubic carbonitride 53wt%, and the remainder is tungsten carbide powder. The particle size of each powder is <1.8 μm. The above raw materials, solvent (using anhydrous ethanol as solvent) and molding agent (using paraffin as molding agent, the addition amount is 2wt% of the total mass of the raw materials) are mixed and ball-milled, and spray granulated to obtain a mixture.

[0075] S2, pressing the mixed material into a compact to obtain a green compact;

[0076] S3. Place the compact in a vacuum atmosphere, heat it to 1200°C, introduce 40 mbar nitrogen partial pressure, then heat it to 1500°C at a heating rate of 6°C / min in a nitrogen atmosphere and sinter it for 90 minutes. Then adjust the nitrogen partial pressure to 20 mbar, adjust the temperature to 1400°C and sinter it for 10 minutes. Then fill it with 5 bar argon atmosphere and cool it to room temperature to obtain a metal ceramic with a double-layer surface structure.

[0077] The metal ceramic with a double-layer surface structure obtained in this embodiment is cut and formed to form a rough tool blank, and the cutting edge of the tool is rounded using a nylon brush containing SiC. Thereafter, an AlCrN+TiSiN nano-alternating coating (nanolayer thickness is 50 nm, coating thickness is 4 μm) is deposited on the surface of the substrate to obtain tool A3.

[0078] Example 4

[0079] A method for preparing a metal ceramic having a double-layer surface structure comprises the following steps:

[0080] S1. The raw materials include cobalt powder and nickel powder as binder phase powder, titanium-containing cubic carbonitride powder and carbide powders of tungsten, tantalum, niobium, molybdenum and vanadium as hard phase powders. The mass percentage of each raw material is as follows: binder phase powder (the mass ratio of cobalt powder and nickel powder is 1:1) 15wt%, tantalum and niobium carbide powders (the mass ratio of tantalum carbide and niobium carbide is 2:1) 15wt%, molybdenum carbide powder 3wt%, vanadium carbide powder 2wt%, titanium-containing cubic carbonitride 53wt%, and the remainder is tungsten carbide powder. The particle size of each powder is <1.8 μm. The above raw materials, solvent (using anhydrous ethanol as solvent) and molding agent (using paraffin as molding agent, the addition amount is 2wt% of the total mass of the raw materials) are mixed and ball-milled, and spray granulated to obtain a mixture.

[0081] S2, pressing the mixed material into a compact to obtain a green compact;

[0082] S3. The compact is placed in a vacuum atmosphere, heated to 1200°C, introduced with a nitrogen partial pressure of 40 mbar, and then sintered to 1470°C at a heating rate of 6°C / min in a nitrogen atmosphere, and kept warm for 90 minutes. Thereafter, the nitrogen partial pressure is adjusted to 20 mbar, the temperature is adjusted to 1400°C and sintered for 10 minutes. Thereafter, a 5 bar argon atmosphere is filled and cooled to room temperature to obtain a metal ceramic with a double-layer surface structure.

[0083] The metal ceramic with a double-layer surface structure obtained in this embodiment is cut and formed to form a rough tool blank, and the cutting edge of the tool is rounded using a nylon brush containing SiC. Thereafter, an AlCrN+TiSiN nano-alternating coating (nanolayer thickness is 30 nm, coating thickness is 3 μm) is deposited on the surface of the substrate to obtain tool A4.

[0084] Comparative Example 1

[0085] The difference from Example 1 is that in step S3, the temperature is raised to 1450° C. under vacuum atmosphere, then switched to 50 bar high-pressure argon atmosphere, kept at 1450° C. for 0.5 h, and then cooled to room temperature.

[0086] The metal ceramic (homogeneous black core phase without gradient) obtained in this comparative example was wet-sandblasted at an angle of 45° to the front cutting edge of the blade to round the blade edge, and then the same coating as in Example 1 was deposited on the surface of the substrate to obtain tool B1.

[0087] Comparative Example 2

[0088] The difference from Example 1 is that in step S3, heating is carried out in a vacuum atmosphere, and after the sintering temperature is increased to 1280°C, 50 mbar nitrogen is filled in and kept warm for 1 hour, and the temperature is further increased to 1470°C in nitrogen, and then kept warm for 2 hours in a 10 MPa argon atmosphere, and then cooled to room temperature.

[0089] The metal ceramic (single gradient: surface layer rich in black core hard phase) obtained in this comparative example was wet sandblasted at an angle of 45° to the front cutting edge of the blade to round the blade edge, and then the same coating as in Example 1 was deposited on the surface of the substrate to obtain tool B2.

[0090] The comparative test data and test results of the above embodiment and comparative example under different cutting conditions are as follows:

[0091] The wear resistance of the blades prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-2 was compared and tested by longitudinal turning of 40CrNi2Mo steel bars. The tool life standard is the processing time when the back tool wear is 0.3 mm. The cutting conditions are shown in Table 1:

[0092] Table 1

[0093]

[0094] The test results are detailed in Table 2:

[0095] Table 2

[0096]

[0097] The comparative test data and test results of the above embodiment and comparative example under different cutting conditions are as follows:

[0098] The impact performance of the tools prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-2 was compared and tested by longitudinally turning a 40CrNi2Mo four-groove steel bar. The tool life standard is the machining time when the back tool wear is 0.3 mm. The cutting conditions are shown in Table 3:

[0099] Table 3

[0100]

[0101] The test results are detailed in Table 4:

[0102] Table 4

[0103]

[0104] The test results show that:

[0105] In the high-speed turning processing of steel, the continuous cutting life of the tool prepared by the embodiment of the present invention is equivalent to that of the control example, but in the intermittent impact test, the tool prepared by the embodiment of the present invention is significantly improved in the impact resistance test than that of the control example; the metal ceramic described in the present invention includes a first surface zone, a second surface zone, and a homogeneous zone from the outside to the inside; the first surface zone presents a core-ring structure with a relatively poor black core and grains with an equiaxed crystal morphology; the second surface zone presents relatively rich black grains, and some grains are core-core structures; the homogeneous zone presents a uniformly distributed core-ring structure. The first surface zone has a relatively black-poor core and a core-ring structure with equiaxed crystal morphology, and the organizational composition has high solid solubility of elements such as W, Ti, Ta, Nb, and V. This structure has a high thermal vibration resistance gradient in the material, which reduces the probability of micro-chipping when the tool contacts the workpiece in the initial cutting stage, and hinders the extension of the crack phase inside the material; the second surface zone has relatively black-rich grains, and some grains are core-core structures. The carbide, nitride, and carbonitride phases of Ti make the material structure have a high wear resistance gradient. During continuous and stable cutting, the second surface zone can ensure a good cutting life of the tool; the homogeneous zone has a uniformly distributed core-ring structure that has both hardness and chipping resistance, maintaining the good comprehensive performance of the material.

[0106] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A metal ceramic having a double-layer surface structure, characterized in that: The metal ceramic includes a first surface layer area, a second surface layer area, and a homogeneous area from the outside to the inside; The first surface layer has a core ring structure with a relatively poor black core and grains of equiaxed crystal morphology, and the equiaxed crystal morphology refers to a grain aspect ratio of 1.0 to 1.8; the thickness of the first surface layer is 2 to 10 μm; the average size of the grains in the first surface layer is 1 to 3 μm; The second surface layer has relatively rich black grains, and some of the grains are core-core structures; the thickness of the second surface layer is 0.5~5.0μm; the grain size of the second surface layer is 0.6~1.5μm; The homogeneous area presents a uniformly distributed core ring structure.

2. The metal ceramic with a double-layer surface structure according to claim 1, characterized in that: The core-ring structure of the homogeneous zone is a black core-gray ring structure or a white core-gray ring structure.

3. The metal ceramic with a double-layer surface structure according to claim 1, characterized in that: At least one layer of nano-alternating layer of AlCrXN and TiSiMN, or at least one layer of nano-alternating layer of AlCrN and TiSiMN, or at least one layer of nano-alternating layer of AlCrXN and TiSiN is coated outside the first surface layer; X is at least one of C, O, B, Si, Ti, Zr, Hf, V, W, Y, and Ce; M is at least one of C, O, B, Al, Zr, Hf, V, W, Y, and Ce; the thickness of the nano-alternating layer is 20-50 nm, and the total thickness of the coated coating is 2-4 μm.

4. The metal ceramic with a double-layer surface structure according to claim 1, characterized in that: The homogeneous zone hardness of the metal ceramic with a double-layer surface structure is HRA 90.8-91.6; the first surface zone hardness is HRA 90.4-91.2; and the second surface zone hardness is HRA 91.2-92.

0.

5. A method for preparing a metal ceramic having a double-layer surface structure according to any one of claims 1 to 4, characterized in that: The steps include: S1, mixing the raw materials, solvent and forming agent, ball milling and spray granulation to obtain a mixed material; S2, pressing the mixed material into a compact to obtain a green compact; S3, placing the pressed green sheet under vacuum atmosphere, heating it to the forming agent removal temperature, removing the forming agent, then heating the pressed green sheet from which the forming agent has been removed to A temperature in A atmosphere and sintering, then adjusting the temperature to B temperature in B atmosphere and sintering, and then cooling it to room temperature in C atmosphere to obtain a metal ceramic with a double-layer surface structure; in the step S3, the A atmosphere is a nitrogen partial pressure gas of 10~100mbar; the heating rate is 5~7℃ / min, the A temperature is 1430~1550℃, and the A temperature sintering time is 30~120min; the B atmosphere is a nitrogen partial pressure gas of 2~50mbar, the B temperature is 1350~1400℃, and the B temperature sintering time is 30~60min; the C atmosphere is an argon atmosphere of 2~10bar.

6. The method for preparing a metal ceramic having a double-layer surface structure according to claim 5, characterized in that: The method further comprises step S4, coating at least one nano-alternating layer of AlCrXN and TiSiMN, or at least one nano-alternating layer of AlCrN and TiSiMN, or at least one nano-alternating layer of AlCrXN and TiSiN outside the first surface layer area; X is at least one of C, O, B, Si, Ti, Zr, Hf, V, W, Y, and Ce; M is at least one of C, O, B, Al, Zr, Hf, V, W, Y, and Ce; the thickness of the nano-alternating layer is 20 to 50 nm, and the total thickness of the coated coating is 2 to 4 μm.

7. The method for preparing a metal ceramic having a double-layer surface structure according to claim 5, characterized in that: In the step S1, the raw materials include hard phase powder and binder phase powder, the mass of the hard phase powder accounts for 75-90wt% of the total mass of the raw materials, and the mass of the binder phase powder accounts for 10-25wt% of the total mass of the raw materials; the hard phase powder is selected from at least one of carbide powder, nitride powder or carbonitride powder containing one or more of Ti, W, Ta, Nb, Cr, Mo, V, Mn, Hf and their solid solution powders; the binder phase powder is selected from at least one of cobalt, nickel and iron; the molding agent is selected from at least one of 48#-56# paraffin and PEG1000-PEG20000; and the solvent is anhydrous ethanol.